2001
DOI: 10.4049/jimmunol.166.7.4780
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Anti-Proliferating Cell Nuclear Antigen (PCNA) Murine Monoclonal Antibodies and Human Autoantibodies to the PCNA Multiprotein Complexes Involved in Cell Proliferation

Abstract: Proliferating cell nuclear Ag (PCNA) occurs as a component of multiprotein complexes during cell proliferation. We found the complexes to react with murine anti-PCNA mAbs, but not with anti-PCNA Abs in lupus sera. The complexes were purified from rabbit thymus extract by affinity chromatography using anti-PCNA mAbs (TOB7, TO17, and TO30) and analyzed by ELISA, immunoprecipitation, immunoblotting, and HPLC gel filtration. That PCNA was complexed with other proteins was demonstrated by its copurification with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2002
2002
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
0
24
1
Order By: Relevance
“…Recent studies have shown PCNA to be involved in numerous cellular functions associated with cell proliferation and to directly bind to or interact with various proteins, as listed in Table 1 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)24). Our previous study (24) revealed that the PCNA multiprotein complexes purified by mAb to PCNA contained components of multiprotein machinery such as the DNA replication fork (Figure 1) (12,13,21,22) and a quaternary PCNA/ p21/CDK/cyclin complex reported to play a key role in the regulation of the cell cycle (14,17).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown PCNA to be involved in numerous cellular functions associated with cell proliferation and to directly bind to or interact with various proteins, as listed in Table 1 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)24). Our previous study (24) revealed that the PCNA multiprotein complexes purified by mAb to PCNA contained components of multiprotein machinery such as the DNA replication fork (Figure 1) (12,13,21,22) and a quaternary PCNA/ p21/CDK/cyclin complex reported to play a key role in the regulation of the cell cycle (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study (24) revealed that the PCNA multiprotein complexes purified by mAb to PCNA contained components of multiprotein machinery such as the DNA replication fork (Figure 1) (12,13,21,22) and a quaternary PCNA/ p21/CDK/cyclin complex reported to play a key role in the regulation of the cell cycle (14,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations